IDENTIFYING THE USE OF CONCRETE AND ABSTRACT NOUN IN ARTICLE “NUTRITION AND WEIGHT LOSS MYTHS DEBUNKED FOR A HEALTHIER” BY CATHY CASSATA - Anita Sitanggang (Jurnal Scientia, 2023)
The purpose of this research is to identify the abstract and concrete and nouns used in Cathy Cassata's essay Nutrition and Weight Loss Myths Debunked for a Healthier You. The major purpose of this research was to find abstract and concrete nouns in the article Nutrition and Weight Loss Myths Debunked. An abstract word is a phrase used to describe ideas, feelings, or experiences that our senses may imagine and experience but cannot touch. A tangible noun is a term that can be seen, touched, and observed using our five senses. This research used a descriptive qualitative technique. This research examined and determined the usage of abstract and concrete nouns that appeared most frequently in the article Nutrition and Weight Loss Myths Debunked. This research makes use of descriptive qualitative research. The researcher uses three steps to examine the data: the first is reading the article, the second is discovering and gathering data, and the third is writing all of the data in the paper. According to the conclusions of this research, there are 105 abstract nouns in total, with the most abstract nouns appearing in the unique phrase "Diet" at 17 terms. This work has 36 concrete nouns, with "Kumar" as a person's name being the most concrete.